The Structures of Displacement in Risalat Al-Sahel Wa Al-Shahij - عيسى, حكمت; نمر, مصطفى; علي, فاطمه (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
Abu Al-Alaa Al-Maari has always been a problematic writer; those interested in literature never agreed about him and his writings, and studies are still striving to explore his mysteries. This research can be considered a little contribution to these studies, as it is concerned with tracking the phenomenon of displacement in a book that has not received the attention it deserves; it is Risalat Al-Sahel Wa Al-Shahij, on two axes: horizontal and vertical: the horizontal axis is manifested by the structural displacement which is based on some phenomena on the sentence level, while the vertical axis is manifested by the semantic displacement which is also called substitutional displacement, in order to understand these displacements and their aesthetics.